«Բանք իմաստասիրաց»-ի տարբերակները ԺԴ դարի հայերեն ձեռագիր «Ժողովածոյ»-ներում - Պողոսյան, Ռուզան
The Sayings of the Philosophers have come down to us in several recensions that vary both in the number of sayings and in their content and structure. They can be categorized into two groups: shorter and longer recensions. The longer recensions provide an initial understanding of the original text, upon which the later recensions are based. The article discusses nine 14th-century manuscripts and compares them with four manuscripts from the 13th century. «Изречения философов» дошли до нас в нескольких вариантах, которые различаются как по количеству изречений, так и по содержанию и структуре. Эти варианты можно разделить на две группы: краткие и пространные. Пространные редакции позволяют получить первоначальное представление об оригинальном тексте, на основе которого были составлены более поздние версии. В этой статье рассматриваются девять рукописей XIV века в сопоставлении с четырьмя рукописями XIII века.
Keywords: Բանասիրություն; Ձեռագրեր